Caries and fluorosis in 6- and 9-year-old children residing in three communities in Iran - Meyer-Lueckel H, Paris S, Shirkhani B, Hopfenmuller W, Kielbassa AM. (Blackwell Synergy, 2006)
The aim of this study was to investigate the caries and fluorosis prevalence among 6- and 9-year-old students in three communities in Iran with varying urbanization and fluoride in piped water.